THE REGULATION USING ENGLISH AS AN INTRUCTIONAL LANGUAGE IN NATIONAL PLUS SCHOOL - Muji Endah Palupi (Journal of English Language and Literature (JELL), 2019)
This study aims to explore the implementation of use English as an instructional language at school. School regulations made to train student discipline Regulations must be followed by students in the learning process as a benchmark for achieving goals of success. Students need to know positive things in getting used to communicating, writing, and slogans In the modern era it is required to have the ability to speak English. English is an International Language. Western countries play an important role in the development of science and technology. If want to be an expert scientist, linguist, and able to compete with other countries and people have skills in English. In Indonesia, English is also used as a graduation standard in schools, The National plus Schools are combining between The National Curriculum recommended by The National Education Standards Agency, it was adopted from The OECD Country Curriculum or ASEAN Countries. The language of instruction uses English. Schools have goal of creating superior individuals, globally competitive and international capacity.